Increase in Blood Pressure among Post–spinal Anesthesia Hypotensive Patients Following 30° and 45° Leg Elevation - Maria Diah Cipaningtyas; Yunita Anggraeni; Taufan Arif (FORIKES, 2026)
Spinal anesthesia commonly induces hemodynamic alterations, particularly post–spinal anesthesia hypotension resulting from sympathetic blockade of efferent preganglionic vasomotor fibers. This sympathetic inhibition reduces vascular tone and venous return, leading to a decline in systolic blood pressure. Leg elevation is a simple, non‑pharmacological maneuver that may enhance venous return through gravitational redistribution of blood toward the central circulation. This study aimed to determine the effectiveness of 30° and 45° leg elevation in increasing blood pressure among patients experiencing hypotension after spinal anesthesia. A quasi‑experimental design employing a Three‑Group Pretest–Posttest Control Group Design was used. A total of 30 respondents were selected through purposive sampling and allocated into three groups. Respondents met the inclusion criteria of post–spinal anesthesia hypotension (80 mmHg < systolic ≤ 100 mmHg). The independent variables were 30° leg elevation and 45° leg elevation, while the dependent variable was systolic blood pressure. Statistical analyses included normality testing, homogeneity testing, paired t‑test, independent t‑test, and one‑way ANOVA. The results demonstrated a significant difference in systolic blood pressure following the application of 30° and 45° leg elevation, with a p‑value of 0.000 (p < 0.005) and a mean difference of 12.3 mmHg. The 45° leg elevation produced a greater increase in systolic blood pressure compared to the 30° elevation. In conclusion, leg elevation at 45° is more effective in increasing systolic blood pressure among post–spinal anesthesia hypotensive patients. A higher elevation angle facilitates greater gravitational blood flow toward the heart, thereby enhancing venous return and improving systolic blood pressure.Keywords: 30° leg elevation; 45° leg elevation; blood pressure; hypotension; spinal anesthesia